Engineering Phosphatidylserine Containing Asymmetric Giant Unilamellar Vesicles - Jake McDonough; Trevor A. Paratore; Hannah M. Ketelhohn; Bella C. DeCilio; Alonzo H. Ross; Arne Gericke (Membranes)
The plasma membrane lipid distribution is asymmetric, with several anionic lipid species located in its inner leaflet. Among these, phosphatidylserine (PS) plays a crucial role in various important physiological functions. Over the last decade several methods have been developed that allow for the fabrication of large or giant unilamellar vesicles (GUVs) with an asymmetric lipid composition. Investigating the physicochemical properties of PS in such asymmetric lipid bilayers and studying its interactions with proteins necessitates the reliable fabrication of asymmetric GUVs (aGUVs) with a high degree of asymmetry that exhibit PS in the outer leaflet so that the interaction with peptides and proteins can be studied. Despite progress, achieving aGUVs with well-defined PS asymmetry remains challenging. Recently, a Ca2+-initiated hemifusion method has been introduced, utilizing the fusion of symmetric GUVs (sGUVs) with a supported lipid bilayer (SLB) for the fabrication of aGUVs. We extend this approach to create aGUVs with PS in the outer bilayer leaflet. Comparing the degree of asymmetry between aGUVs obtained via Ca2+ or Mg2+ initiated hemifusion of a phosphatidylcholine (PC) sGUVwith a PC/PS-supported lipid bilayer, we observe for both bivalent cations a significant number of aGUVs with near-complete asymmetry. The degree of asymmetry distribution is narrower for physiological salt conditions than at lower ionic strengths. While Ca2+ clusters PS in the SLB, macroscopic domain formation is absent in the presence of Mg2+. However, the clustering of PS upon the addition of Ca2+ is apparently too slow to have a negative effect on the quality of the obtained aGUVs. We introduce a data filtering method to select aGUVs that are best suited for further investigation.